2021
DOI: 10.1091/mbc.e20-10-0646
|View full text |Cite
|
Sign up to set email alerts
|

The cell polarity kinase Par1b/MARK2 activation selects specific NF-kB transcripts via phosphorylation of core mediator Med17/TRAP80

Abstract: Par1b/MARK2 is a Ser/Thr kinase with pleiotropic effects which participates in the generation of apico-basal polarity in C. elegans. It is phosphorylated by atypical PKC(ι/λ) in Thr595 and inhibited. Because previous work showed a decrease in aPKC activity under pro-inflammatory conditions, we analyzed the hypothesis that resulting decrease in Thr595-MARK2 with increased kinase activity may also participate in innate immunity. We confirmed that pT595-MARK2 was decreased under inflammatory stimulation. Increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…MARK2 then phosphorylates Par3, releasing it from the polarity complex, which results in changes in Par3 cytoplasmic distribution and changes in cellular polarity. It was shown that stimulation of NF-κB/IFN by TNFα and IFNγ leads to the downregulation of aPKC in intestinal epithelial cells resulting in an increase in NF-κB activity and chronic inflammation linked to elevated expression of IL-8 and CXCL1 [ 58 ]. All these observations suggest that NF-κB is linked to EMT-induced downregulation of polarity genes, driving the loss of apical-basolateral polarity.…”
Section: Introductionmentioning
confidence: 99%
“…MARK2 then phosphorylates Par3, releasing it from the polarity complex, which results in changes in Par3 cytoplasmic distribution and changes in cellular polarity. It was shown that stimulation of NF-κB/IFN by TNFα and IFNγ leads to the downregulation of aPKC in intestinal epithelial cells resulting in an increase in NF-κB activity and chronic inflammation linked to elevated expression of IL-8 and CXCL1 [ 58 ]. All these observations suggest that NF-κB is linked to EMT-induced downregulation of polarity genes, driving the loss of apical-basolateral polarity.…”
Section: Introductionmentioning
confidence: 99%